Optimizing stress ulcer prophylaxis practices and reducing associated costs in intensive care units: a non-randomized controlled study - Yunus Emre Ayhan; Güneş Eskidemir; Ayşe Gül Koçoğlu Kınal; Nilay Aksoy (Journal of Pharmacy & Pharmaceutical Sciences)
ObjectiveThis study evaluated the use of stress ulcer prophylaxis (SUP), assessed the costs associated with inappropriate use, and highlighted the impact of clinical pharmacists on improving adherence to the SUP guidelines.MethodA prospective, non-randomized controlled study was carried out in two intensive care units (ICUs) of a training and research hospital between 1 June 2023 and 1 December 2023. Routine care services were provided for the observation group (OG) patients. In the guideline group (GG) patients, SUP management and routine care were performed according to ASHP guidelines. The physician and clinical pharmacist jointly evaluated the patients to determine the suitability of their SUP indications. Adherence rates to ASHP guidelines and the costs associated with nonadherence were evaluated.ResultsA total of 196 patients were included in the study: 121 in the OG and 75 in the GG. A total of 54.6% of the patients were male, and the reason for hospitalization was mainly surgery (52.6%). SUP use was higher in OG (100%) than in GG (42.6%) (p < 0.001). The indication rate according to the ASHP guidelines was significantly higher in the GG group (100%) than in the OG group (54.5%) (p < 0.001). Dosage form adherence was significantly lower in the OG (0%) than in the GG (100%) (p < 0.001). The costs associated with proton pump inhibitor use for inappropriate indications and incorrect dosage forms were $60 versus $0 (p < 0.001) and $321 versus $0 (p < 0.001) in OG and GG, respectively. Overall, cost savings of $327 were achieved in the GG group.ConclusionInappropriate SUP use is common in the ICUs. Adequate adherence to guidelines and proactive involvement of clinical pharmacists may reduce inappropriate SUP in ICUs and the associated costs.